Gallbladder adenocarcinoma presenting as Trousseau syndrome and Virchow-Troisie’s node - Vargas-Rubio, Víctor A. (2020)
A 52-year-old female patient who presented pain and swelling in the right lower limb, a left-sided supraclavicular lymph node and microcytic hypochromic anemia. It was ruled out gastrointestinal blood loss through normal upper and lower endoscopies. The abdominal tomography showed an irregular pattern in the gallbladder, whose biopsy resulted in adenocarcinoma. It is concluded that it was a patient with a malignant neoplasm of the gallbladder who presented as a Trousseaus’s syndrome and a Virchow-Troisier’s lymph node.